Exploring the usage of conventional logbooks during the clinical learning practice: A phenomenological study - Winny Setyonugroho; Nurvita Risdiana; Amirul Auzar Ch.; Fatiah Handayani; Muhammad Dian Saputra Taher; Akhmad Khanif (Jurnal Keperawatan Padjadjaran, 2023)
Background: The use of a logbook during practice serves as a tool for ongoing assessment, continuous interaction between supervisors and students, and provides continuous feedback for learning activity evaluation Purpose: This research aims to explore the utilization of logbooks in clinical practice among nursing students. Methods: This qualitative research uses a phenomenological  study approach. Data collection was conducted through open interviews to synchronize informant responses with the observed phenomena. Snowball sampling technique was used to select six students, one responsible lecturer for field practice, and one field supervisor. The obtained data were then processed and analyzed through editing, data reduction, category creation, and drawing conclusions. Results: Four research themes emerged, namely an exploration of clinical practice and the obstacles experienced by students, the importance of logbooks for students, the weaknesses of paper-based logbooks, and student acceptance of online-based logbooks. Conclusions: Nursing profession  students need   the development of a logbook that is easier to fill out. The design of the logbook can be digitally developed with attractive and innovative features while still reflecting the communication medium between students, faculty, and the field. It should also serve as a tool for evaluating students' competencies in their professional roles.